Women's Rights and the Gender Migration Gap - Jerg Gutmann; Léa Marchal; Betül Simsek (Center for Economic Studies and ifo Institute (CESifo), 2023)
This is the first global study of how institutionally entrenched gender discrimination affects the gender migration gap (GMG) using data on 158 origin and 37 destination countries over the period 1961-2019. We estimate a gravity equation derived from a random utility maximization model of migration that accounts for migrants' gender. Instrumental variable estimates indicate that increasing gender equality in economic or political rights generally deepens the GMG, i.e., it reduces female emigration relative to that of men. In line with our theoretical model, this average effect is driven by higher-income countries. In contrast, increased gender equality in rights reduces the GMG in lower-income countries by facilitating female emigration.
Keywords: F22; J16; J71; K38; O15; P48; 330; discrimination; gender equality; individual rights; migration; RUM model